The Effect of Back Massage on Labor Pain in Phase I Active in Maternity Mothers at PMB Intan In Tangerang District 2022 - Ismarina; Prihayati; Marthia Ikhlasiah; Kurniahawa Arta (KHD-Production, 2023)
Background:The most important midwifery care in the delivery process is to apply the principle of